Welfare Scheme for Domestic Migrant Workers in the Analysis of Kerala - Haseena V.A (Public Policy and Administration Research, 2015)
Kerala state, which accounts for 1.18 per cent (38863 square kilometres) of the total land area of India, accommodates 3.1 per cent (34 million) of the Indian population. The development experience of Kerala is characterised by high social development disproportionate to the level of economic growth 2 . The experience, often described as the Kerala model of development, has received world wide attention from both scholars and development agencies. The achievements of Kerala, going at least by macro level indicators of social development, have exceeded those of other Indian states 3 and some of the developed countries. The state is ranked first among the states in India on the basis of human development index and rural social development index. The state has also been successful in reducing poverty which is 13.7 per cent and 14.7 per cent in rural and urban areas respectively in 2004-05 while the corresponding figures for India was 28.7 per cent and 25.9 per cent (Tendulkar, 2009). The state's development pattern also indicates relatively low inequalities in health and education outcomes. Nobel laureate Amartya Sen cites Kerala as a case of support led security as against the growth mediated security